ECONOMIC CONDITION OF SMALL AND MEDIUM ENTERPRISES FROM RURAL AREAS OF WARMIA AND MAZURY - Ratajczak, Marcin (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents the economic condition of small and medium-sized enterprises in rural areas of Warmia and Mazury, especially regarding their average economic and financial results, as well as the gross profitability of the surveyed firms. Author also identified the statistical relationship between the section of the economy and profits of the surveyed companies. Author used his own studies, covering the period 2005–2007. The analysis shows that the economic condition of small and medium-sized enterprises largely depends on the type of economic activities they carry out and the development opportunities.